Comparative Efficacy and Safety of Colchicine and Anti–Interleukin‐1 Agents in Recurrent Pericarditis: A Pairwise and Network Meta‐Analysis of Randomized Controlled Trials - Muhammad Ehsan; Alveena Batool Syed; Biah Mustafa; Jibran Ikram; Muhammad Hammad Khan; Paul C. Cremer; Massimo Imazio; Tom Kai Ming Wang; Allan L. Klein (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background The management of recurrent pericarditis includes colchicine and anti–interleukin‐1 agents, given the limited efficacy and adverse effects of NSAIDs and corticosteroids. We conducted a pairwise and network meta‐analysis to evaluate the efficacy and safety of colchicine and anti–interleukin‐1 agents in recurrent pericarditis. Methods We conducted a comprehensive search on various databases to retrieve relevant randomized controlled trials. Pairwise meta‐analyses were performed in R using the exact Mantel–Haenszel method. We also performed a network meta‐analysis with a colchicine group as the comparator. Results A total of 6 randomized controlled trials were included in the meta‐analysis. The risk of pericarditis recurrence was significantly decreased by colchicine (risk ratio [RR], 0.46 [95% CI, 0.37–0.58]) and anti–interleukin‐1 agents (RR, 0.12 [95% CI, 0.03–0.54]) compared with placebo or standard therapy. Colchicine significantly decreased the risk of treatment failure (RR, 0.42 [95% CI, 0.31–0.57]) and pericarditis‐related rehospitalization (RR, 0.26 [95% CI, 0.10–0.70]) but did not have a significant impact on the risk of adverse events (RR, 1.06 [95% CI, 0.31–3.62]). Anti–interleukin‐1 agents were associated with a significantly increased risk of adverse events (RR, 1.88 [95% CI, 1.60–2.21]). The network meta‐analysis showed that anti–interleukin‐1 agents were associated with a greater reduction in pericarditis recurrence than colchicine (RR, 0.27 [95% CI, 0.11–0.67]), with no significant difference with respect to adverse events (RR, 1.77 [95% CI, 0.88–3.57]). Conclusions Both colchicine and anti–interleukin‐1 agents are effective in reducing the risk of recurrent pericarditis. Anti–interleukin‐1 agents are associated with more frequent nonserious adverse events, but evidence on serious adverse events remains inconclusive.